VENA DETECTORS OBJECT EFFECTIVELY CONTROLS PAIN IN CHILDREN DURING INFUSION INSTALLATION - Andayani, Rifka Putri (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
The vascular access procedure is a common procedure for treated children. Children need vascular access for various indications. Children who are hospitalized will receive treatment and care according to their basic needs and illness. One of the routine actions is infusion. Determination of venous location to be infused is a process that must be done first, to improve vein visualization, the use of infrared systems can be used to assist in the process of dilation of blood vessels. This study aims to determine the effect of venous detectors on pain response in children who performed infusion. The design of this study is a quantitative study with a quasi-experimental approach to pre-test and post-test nonequivalent control group design on 20 respondents. This study consisted of 2 groups: an intervention group and a control group. The intervention group was measured before stabbing during infusion (pre-test) and measured after infusion (post-test). Whereas in the control group no intervention was carried out but pre-test and post-test measurements were taken. The results showed there was a difference between the pain scores before and after the infusion was performed with a p value <0.001. The use of vein detectors is effective in reducing pain in children during infusion.